Terror in the mind of God the global rise of religious violence - Juergensmeyer, Mark 1940- (University of California Press, 2003)
Since September 11, 2001, we all need tools to help us understand what motivates religious terrorism. In this wide-ranging and erudite book, Mark Juergensmeyer asks one of the most important and perplexing questions of our age: Why do religious people commit violent acts in the name of their god, taking the lives of innocent victims and terrorizing entire populations? This, the first comparative study of religious terrorism, explores incidents such as the World Trade Center explosion, Hamas suicide bombings, the Tokyo subway nerve gas attack, and the killing of abortion clinic doctors in the United States. Updated with a new preface addressing the events of September 11, the book incorporates personal interviews with World Trade Center bomber Mahmud Abouhalima, Christian Right activist Mike Bray, Hamas leaders Sheik Yassin and Abdul Azis Rantisi, and Sikh political leader Simranjit Singh Mann, among others, Juergensmeyer takes us into the mindset of those who perpetrate and support violent acts. In the process, he helps us understand why these acts are often associated with religious causes and why they occur with such frequency at this moment in history. Terror in the Mind of God places these acts of violence in the context of global political and social changes, and posits them as attempts to empower the cultures of violence that support them. Juergensmeyer analyzes the economic, ideological, and gender-related dimensions of cultures that embrace a central sacred concept--cosmic war--and that employ religion to demonize their enemies. Juergensmeyer's narrative is engaging, incisive, and sweeping in scope. He convincingly shows that while, in many cases, religion supplies not only the ideology but also the motivation and organizational structure for the perpetrators of violent acts, it also carries with it the possibilities for peace. Los Angeles Times Best Nonfiction Book of 2000
Keywords: Geweld; Godsdienst; Terrorisme; Gewalt; Religion; Terrorismus; Violence -- Religious aspects; Gewalttätigkeit; Religiöse Bewegung; Fundamentalismus